Effect of daidzein on Parkinson disease induced by reserpine in rats - Radha Goel; Rabia Chaudhary (Universidade de São Paulo, 2020)
Parkinson disease is a neurodegenerative disorder characterised by the cardinal symptoms of stiffness, resting tremor, slowness (bradykinesia) and reduction of movement (hypokinesia). Involvement of oxidative damage has been reported in the pathophysiology of Parkinson disease and its related complications. The purpose of this study was to examine the effect of daidzein to quench the free radicals produced as a result of the increased oxidative stress in Parkinson disease.Parkinson disease is induced by administration of reserpine (5 mg/kg/day, i.p) for 5 consecutive days. The symptoms of PD such as tremors, akinesia and rigidity were evaluated. The effect was evaluated by assessing various behavioral parameters (grip strength and locomotor activity), biochemical parameters (lipid peroxidation, and reduced glutathione), as well as histopathological parameters in brain tissue. Daidzein (an antioxidant) was administered at the dose of 50 and 100 mg/kg, p.o. once daily for 5 days. Reserpine significantly causes tremor, rigidity, akinesia and oxidative damage which were reversed by daily administration of daidzein when compared toreserpine group. There was a significant histological improvement in the neuronal degeneration in brain tissue with daidzein. So, the results indicated the protective effect of daidzein against PD.